Integrating Human Rights into Development : Donor Approaches, Experiences and Challenges, Third Ed. - World Bank; Organisation for Economic Co-operation and Development (Washington, DC: World Bank, 2017)
This study, originally published in 2006 and updated in 2011, is being updated in this third edition. The work was originally based on a study commissioned by the Organization for Economic Co-operation and Development (OECD) Development Assistance Committee (DAC) Network on Governance (GOVNET), which reviewed the approaches of different donor agencies and their rationales for working on human rights. The third edition reviews the current practice in the field and draws together experiences that form the core of the current evidence around the contribution of human rights to development. It discusses both new opportunities and conceptual and practical challenges to human rights that concern the development partnerships between donors and partner countries, and the workings of the international aid system more broadly. This edition includes recent developments in the area of human rights, aid effectiveness, and sustainable development. Of continued relevance to this publication is the OECD DAC 2007 Action-Oriented Policy Paper, which affirmed unequivocally that human rights are an essential part of development cooperation, noting the increasing convergence of the two areas and the relevance of human rights considerations to aid effectiveness: the 2008 Accra agenda for action and 2011 Busan outcome document both acknowledged the importance of human rights standards and principles. In the context of the Millennium Development Goals (MDGs), the 2010 UN World Summit outcome document confirmed the centrality of human rights to sustainable development that paved the way for the 2015 Sustainable Development Goals (SDGs). Finally, in the sphere of business and human rights, the 2013 adoption of the Guiding Principles on Business and Human Rights by the UN Human Rights Council, although of more indirect relevance to donor policies, signaled a rapprochement in terms between the worlds of finance and investment on the one hand and human rights on the other. The links among rights violations, poverty, exclusion, environmental degradation, vulnerability, and conflict in more applied terms have continued to be explored. There is growing recognition of the intrinsic importance of human rights in a range of contexts, as well as their potential instrumental relevance for improved development processes and outcomes and a sustained interest in tools and metrics, including human rights indicators.